EDUKASI DAN PELATIHAN SKRINING STUNTING PADA IBU MEMILIKI BAYI DAN BALITA MELALUI PEMBERDAYAAN KADER DAN TENAGA KESEHATAN DI KELURAHAN MUARA RAPAK BALIKPAPAN UTARA - Grace Carol Sipasulta; Rus Andraini; Endah Wijayanti; Genevieva Esmeraldine Tanihatu (J-ABDI: Jurnal Pengabdian kepada Masyarakat, 2024)
Stunting is not just about height; it is very dangerous as it lowers children's learning abilities and causes mental retardation, as well as the emergence of chronic diseases, impacting both social and economic aspects. Effectively addressing stunting requires a holistic approach involving the government and the relevant community. In the Muara Rapak Village, North Balikpapan District, there are 15 cases of stunting among infants and toddlers, 10 pregnant women with anemia, 10 pregnant women with KEK, and 44 pregnant women at risk of stunting. In addition, the participation of Kelurahan partners such as cadres and community groups in the prevention and control of stunting has not been optimal. The general objective of this community service activity is to enhance the knowledge and services of partner targets regarding stunting prevention and control screening through Posyandu: Stunting Screening Training, as well as local ingredient-based "MPASI" and "PMBA". The method used includes educating mothers at the posyandu about stunting and measuring height and weight, training health cadres to prevent stunting, and making complementary foods and local-based baby food. The target health cadres in Muara Rapak Village, North Balikpapan District, have not yet received training and introduction to stunting prevention, totaling 40 people, as well as mothers with infants and toddlers. There are 2 out of 22 children aged 1 and 2 years who did not experience an increase in weight and require parental attention to ensure this does not occur in two consecutive months of weighing. Training helps health cadres improve their knowledge about stunting prevention. The average knowledge before education was 47.75% and after education was 90.15%, resulting in a knowledge increase of 70%. The preparation of complementary feeding (MPASI) and breastfeeding (PMBA) went well, with the food prepared for babies aged 6 months to 1 year being directly given to 11-month-old babies under observation, who enjoyed the food given. Evaluation over two months on the use of the Anthropometry Kit showed a 100% improvement, and the measurement of TB, BB of infants, toddlers, and the provision of MPASI and PMBA at the Posyandu also showed improvements. The increase in cadre knowledge is very much needed to prevent stunting with good screening